A heuristic method for feeder reconfiguration and service restoration in distribution networks - Singh S.P.; Raju G.S.; Rao G.K.; Afsari M. (My University, 2025)
A sequential switch opening method is proposed for minimum loss feeder reconfiguration in this paper. The algorithm is further extended for service restoration. The method is based on the branch power flow rather than the current flow as reported in earlier methods. The final algorithm arrives at opening of a branch in a loop carrying minimum resistive power flow to make the network radial causing minimum loss. The test results reveal that the proposed method yields optimal configuration with reduced computation burden and better restoration plan. © 2009 Elsevier Ltd. All rights reserved.